Synthetic and Structural Study on Orthometallated Ferrocene Complexes: Non‐Planar Metallabenzene and Five‐Membered Metallacycle Complexes with Closed Os3 Triangles. Issue 26 (5th July 2018) - Tauqeer, Mohd.; Ji, Radhe Shyam; Singh, Amrendra K.; Mobin, Shaikh M.; Lahiri, Goutam K.; Mathur, Pradeep
Abstract : Thermolysis of ( Z )‐1‐ferrocenyltelluro‐1‐ferrocenyl‐4‐ferrocenyl‐1‐buten‐3‐yne with [Os3 (CO)12 ] in toluene gave two new clusters: non‐planar six‐membered metallacycle complex [Os3 H(CO)7 (µ3 ‐Te){η 1 :η 1 :η 2 :η 2 ‐FcCCC(H)(Fc)2 }] (1, Fc = ferrocenyl) and five‐membered cyclometallated ring complex [Os3 (CO)7 (µ3 ‐Te){η 1 :η 1 :η 3 ‐FcC(H)C(H)CC(Fc)2 }] (2 ). Compounds1 and2 may be thought to form by orthometallation of ferrocene with a closed Os3 triangle by intramolecular rearrangement of atoms within the cluster complexes. Typically the formation of a non‐planar metallabenzene such as1 may involve the orthometallation of another aromatic ring. Also, conversion of1 to2 shows the initial step required for alkene hydrogenation by a tellurium‐bridged triosmium cluster. Both compounds were characterized by IR and 1 H NMR spectroscopy, and their structures established by single‐crystal XRD. Abstract : [Os3 H(CO)7 {µ3 ‐Te–η 1 :η 2 :η 1 :η 1 ‐FcCCC(H)C(Fc)2 }] having a non‐planar six‐membered cyclometallated ring and [Os3 (CO)7 {µ3 ‐Te–η 1 :η 1 :η 2 :η 2 ‐FcC(H)C(H)CC(Fc)2 }] with a five‐membered cyclometallated ring were obtained by thermolysis of ( Z )‐1‐ferrocenyltelluro‐1‐ferrocenyl‐4‐ferrocenyl‐1‐buten‐3‐yne with [Os3 (CO)12 ]. These compounds are the result of rare orthometallation of ferrocene with an Os3 metal carbonyl triangle.